Unexpected Complication Ten Years after Initial Treatment: Long-Term Report and Fate of a Maxillary Premolar Rehabilitation - Davide Augusti; Gabriele Augusti (Case Reports in Dentistry)
Full-coverage restorations represent a well-known rehabilitation strategy for compromised posterior teeth; in the last years, new ceramic materials like zirconia have been introduced and widely adopted for the prosthetic management of molar and premolar areas. A long-term follow-up of a maxillary premolar rehabilitation using a veneered zirconia crown is presented; after ten years of uneventful clinical service of the tooth-restoration complex, a serious complication—namely, a vertical root fracture (VRF)—occurred. An extended time lapse (9 years) between the end of restorative procedures and development of symptoms due to VRF has been observed. On the other hand, a complete functional and esthetic integrity of the zirconia crown (without chippings or crack development) is documented along the follow-up period. Due to periodontal breakdown and severity of fracture, the premolar was extracted. The illustrations of our late failure, aetiological factors, and available data on the literature regarding VRF are addressed. Patients and clinicians should be aware of potential occurrences of some long-term, serious complications when dealing with previously treated and/or structurally weakened teeth. The development of a VRF might be unexpected and might occur many years after the end of tooth rehabilitation, despite adoption of contemporary restorative protocols and techniques.